(untitled) (The International Journal for Scientific Research, 2023)
The study aimed to identify the concepts associated with academic advising from the students’ point of view at Taibah University, the actual practices, and the obstacles facing this process. The study followed the descriptive analytical approach, and the study tool used was a questionnaire that includes three axes, the first axis to determine the availability of academic counseling concepts for students, the second axis to describe the actual practice of academic advising, and the third axis to identify academic advising problems. The sample of the study was 300 students from the last year (in its two semesters) in the faculties of Taibah University. The correct response rate was 65% of the number of students surveyed, based on which statistical calculations were performed using the SPSS program. Then the study data were analyzed, the results and recommendations were accessed and discussed. The results of the study showed a low level of students’ knowledge of the concepts, objectives, and benefits of academic advising. The results of the study also indicated that there are problems in academic advising practices, such as: the student’s lack of attention to the dates of addition and deletion, the lack of more than one channel to raise awareness of the importance and objectives of academic advising, and the lack of clarity in some academic counseling concepts for some academic advisors. The study concluded with a set of recommendations to improve the performance of the academic advising process.